PHYSICO - CHEMICAL STUDIES ON ANTHERAEA MYLITTA DRURY COCOON SHELL (SATURNIIDAE : LEPIDOPTERA) - BARI, ABDUL; RAO, A. PURUSHOTHAM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
The dissolution of cocoon shell of different ecoraces measured using distilled water, ethyl alcohol, acetone and methyl alcohol. The thickness of the cocoon shell based on melting and the time required for saturation among the different ecoraces were found in the order of Andhra local having maximum thickness of the shell followed by Resham. Modal and the least was Ampatia.